Designing Miniature Pot Gardens Using Indonesian Medicinal Plants: An Architectural and Floristic Perspective - Diah Rahayu Purwandari (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the architectural and floristic characteristics of medicinal plants in the Purwodadi Botanical Gardens collection, assess the aesthetic potential of plants as components of miniature gardens in pots of various sizes, and evaluate the level of public appreciation for miniature garden designs based on local Indonesian medicinal plants. Methodology: The research employed descriptive and experimental methods at the Purwodadi Botanical Gardens. Data were obtained through field observations, an inventory of medicinal plant collections, analysis of morphological and floristic characteristics, design of miniature garden models in large, medium, and small pots, and a questionnaire survey of 170 respondents. The tools used included a camera, clay and rubber pots, organic planting media, observation sheets, and an aesthetic evaluation instrument. Main Findings: Eleven types of medicinal plants have high aesthetic value based on their branches, leaves, flowers, and fruit. The medium-sized miniature garden pot model received the highest public appreciation and the most stable aesthetic value. The large-pot model showed increased appreciation after further evaluation, while the small-pot model experienced a decline due to changes in plant conditions. The beauty of the garden is influenced by the appropriateness of plant size, visual combinations, color variations, and optimal use of space. Novelty/Originality of this study: The novelty of this research lies in the integration of medicinal plant architecture analysis, floristic composition, pot-based miniature garden design, and community perception evaluation in a single integrated approach.